The effectiveness of regular leisure-time physical activities on long-term glycemic control in people with type 2 diabetes: A systematic review and meta-analysis. (March 2016) - Pai, Lee-Wen; Li, Tsai-Chung; Hwu, Yueh-Juen; Chang, Shu-Chuan; Chen, Li-Li; Chang, Pi-Ying
Highlights: The results indicated yoga was the most effective method in lowering HbA1c levels. The HbA1c levels of experimental group were 0.60% which was lower than control group. The higher frequency of these activities was the more effective in reducing HbA1c levels. Abstract: The objective of this study was to systematically review the effectiveness of different types of regular leisure-time physical activities and pooled the effect sizes of those activities on long-term glycemic control in people with type 2 diabetes compared with routine care. This review included randomized controlled trials from 1960 to May 2014. A total of 10 Chinese and English databases were searched, following selection and critical appraisal, 18 randomized controlled trials with 915 participants were included. The standardized mean difference was reported as the summary statistic for the overall effect size in a random effects model. The results indicated yoga was the most effective in lowering glycated haemoglobin A1c (HbA1c) levels. Meta-analysis also revealed that the decrease in HbA1c levels of the subjects who took part in regular leisure-time physical activities was 0.60% more than that of control group participants. A higher frequency of regular leisure-time physical activities was found to be more effective in reducing HbA1c levels. The results of this review provide evidence of the benefits associated with regular leisure-time physical activities compared with routine care for lowering HbA1c levels in people with type 2 diabetes.